2011
DOI: 10.1136/hrt.2011.225466
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein cholesterol as a predictor of clinical outcomes in patients achieving low-density lipoprotein cholesterol targets with statins after percutaneous coronary intervention

Abstract: BackgroundA low level of high-density lipoprotein cholesterol (HDL-C) is strongly associated with cardiovascular events. However, the significance of HDL-C after statin therapy on the outcome of patients who have undergone percutaneous coronary intervention (PCI) with drug eluting stents (DES) is unclear.ObjectivesTo investigate the significance of HDL-C after statin therapy on cardiovascular events in patients with coronary artery disease after DES implantation.MethodsPatients who underwent PCI with DES from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
4
33
0
1
Order By: Relevance
“…[143][144][145][146][147] Frequently seen in patients with CAD, a low HDL level has been well described as an independent risk factor for adverse cardiovascular outcomes in several studies. 142,[148][149][150][151][152] Some of the earliest data on the subject became available from the Framingham Heart Study, in which low HDL was found to be a more potent CAD risk factor than high LDL. 148,150 Recent studies from the current era have shown that HDL levels are inversely related to cardiovascular events, even among patients receiving statin therapy 152 and those with LDL levels aggressively treated to <70 mg/dL.…”
Section: High-density Lipoprotein Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…[143][144][145][146][147] Frequently seen in patients with CAD, a low HDL level has been well described as an independent risk factor for adverse cardiovascular outcomes in several studies. 142,[148][149][150][151][152] Some of the earliest data on the subject became available from the Framingham Heart Study, in which low HDL was found to be a more potent CAD risk factor than high LDL. 148,150 Recent studies from the current era have shown that HDL levels are inversely related to cardiovascular events, even among patients receiving statin therapy 152 and those with LDL levels aggressively treated to <70 mg/dL.…”
Section: High-density Lipoprotein Managementmentioning
confidence: 99%
“…142,[148][149][150][151][152] Some of the earliest data on the subject became available from the Framingham Heart Study, in which low HDL was found to be a more potent CAD risk factor than high LDL. 148,150 Recent studies from the current era have shown that HDL levels are inversely related to cardiovascular events, even among patients receiving statin therapy 152 and those with LDL levels aggressively treated to <70 mg/dL. 151 In addition, moderate increases in HDL appear to be associated with regression of coronary atherosclerosis in statin-treated patients.…”
Section: High-density Lipoprotein Managementmentioning
confidence: 99%
“…The entire patient population was divided into always lower at higher levels of achieved HDL-C 6) . The protective effect of high vs low HDL-C has also been demonstrated in patients achieving LDL-C targets with statins after percutaneous coronary interventions 7) . Very recently, HDL-C levels have been shown to be most closely associated with the presence of CAD assessed by multi-detector row computed tomography, irrespective of statin treatment 8) .…”
Section: Laboratory Testsmentioning
confidence: 96%
“…Moreover, low HDL-cholesterol levels have been reported as predictive of negative clinical outcomes in patients achieving LDL-cholesterol targets with statins after PCI. 21 The therapeutic benefits of contemporary medical treatment with statins for the prognosis of HD patients has still not been elucidated and needs to be optimized in terms of patients' lipid control.…”
Section: Lipid Profiles and Inflammationmentioning
confidence: 99%